PREDICTIVE ANALYTICS IN FINTECH: HOW AI IS RESHAPING ECONOMIC DECISION-MAKING - Munivenkatappa K (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid advancement of artificial intelligence (AI) and machine learning has transformed the financial technology (fintech) sector, with predictive analytics emerging as one of the most influential tools reshaping economic decision-making. Predictive analytics involves using AI-driven models to analyze historical and real-time data to forecast future events, trends, and behaviors. In the context of fintech, this capability is revolutionizing how financial institutions, businesses, and individuals assess risk, manage investments, detect fraud, and personalize financial services. Traditional economic decision-making processes often relied on limited data sets, rigid statistical models, and human expertise, which constrained both the speed and accuracy of financial analysis. By contrast, AI-powered predictive analytics can process vast amounts of structured and unstructured data with remarkable speed, uncover hidden patterns, and generate real-time forecasts. This enables more proactive, data-driven decision-making, allowing stakeholders to anticipate market fluctuations, detect emerging risks, and optimize financial strategies. The impact of predictive analytics is evident across various fintech applications, including credit scoring, fraud detection, algorithmic trading, customer relationship management, and regulatory compliance. It has also played a significant role in promoting financial inclusion by leveraging alternative data sources to extend credit to previously underserved populations. However, the increasing reliance on AI and predictive models presents challenges, particularly regarding data privacy, algorithmic bias, and regulatory oversight. This paper explores how predictive analytics, driven by AI, is fundamentally reshaping economic decision-making in fintech. It examines real-world applications, benefits, and associated risks while highlighting the need for responsible AI practices to ensure fairness, transparency, and inclusivity. As the fintech landscape continues to evolve, predictive analytics will remain a key driver of innovation, offering significant opportunities for efficiency, growth, and financial democratization.